Social customer relationship management (S-CRM) among small and medium-sized enterprises (SMES) in Malaysia / Nurun Nasuha Mahmud - Mahmud, Nurun Nasuha (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
Basically, this article focused on the interaction and relationship among small and medium-sized enterprises (SMEs) own by Muslim community with their customers especially in Malaysia. Besides, this article highlighted some benefits and advantage of social relationship management (s-CRM) performance by the business entities especially those who are owned by the Muslim people. The construction of s-CRM is critical to improving business performance and sustaining in the marketplace, as it has substantial implications in marketing, customer care, and sales departments of SMEs.